Effects of autumn plowing on the movement and correlation of moisture, heat and nitrate nitrogen in seasonal freeze-thaw soil - Sun, Kai; Wang, Chunxia; Liu, Hongguang; Liang, Fei; Wang, Yaqin (International Journal of Agricultural and Biological Engineering, 2022)
A two-year experiment was established in the northern Xinjiang to investigate the effects of autumn plowing methods on nitrate nitrogen accumulation, spring-sown soil conditions and cotton emergence rate, and to explore the response relationship between soil water, heat and nitrate nitrogen. The experiment included five autumn plowing treatments, namely, plough tillage (FG), no-tillage (MG), ridge and furrow alternation (LG), plough tillage with straw mulch (FJ) and plough tillage with activated charcoal mulch (FH). The results showed that both FH and FJ treatments were beneficial to promote the nitrate-nitrogen accumulation in topsoil, while FG, MG and LG treatments aggravated the nitrate nitrogen leaching in topsoil. During the freezing period, FH and FJ treatments were beneficial to reduce soil heat loss and facilitate the coordinated upward migration of soil water and nitrate nitrogen. In the thawing period, FH and FJ treatments favored suppressing the synergistic downward transport of soil water and nitrate-nitrogen and motivated the synergistic upward migration of heat and nitrate nitrogen in deep soil. Binary regression analysis suggested that the interaction between water, heat and nitrate nitrogen under FH and FJ treatments showed a highly significant correlation. FH and FJ treatments showed obvious advantages in regulating soil conditions and optimizing soil water, heat and nitrate nitrogen co-transport mechanism. During the spring sowing period, the FH and FJ treatments increased the average soil temperature by 0.99°C and 1.29°C, and the average soil moisture content by 6.01% and 8.70%, and the average soil nitrate content by 10.20 mg/kg and 10.47 mg/kg, in the 0-25 cm soil layer, respectively. FH and FJ treatments significantly grew the emergence rate of cotton, which can be used as the main autumn tillage strategies in arid areas of northern Xinjiang.Keywords: autumn plowing, seasonal freeze-thaw, nitrate nitrogen accumulation, water-heat-nitrogen interaction, XinjiangDOI: 10.25165/j.ijabe.20221506.7269Citation: Sun K, Wang C X, Liu H G, Liang F, Wang Y Q. Effects of autumn plowing on the movement and correlation of moisture, heat and nitrate nitrogen in seasonal freeze-thaw soil. Int J Agric & Biol Eng, 2022; 15(6): 143–152.